Application of terrestrial photogrammetry to the measurement of a riverbank retreat - teruggi, Liliana B.; rinaldi, Massimo; chiaverini, Ivan; Ostuni, Daniele; Dragoni, Walter; Tacconi, Paolo (Italian journal of engineering geology and environment, 2011)
<span data-sheets-value=""1":2,"2":"A detailed study on riverbank retreat is reported with the aim to investigate on advantages and limitations of a high-resolution methodology such as terrestrial photogrammetry, and to quantify the sediment eroded from a representative reach of riverbank during a period of about 30 months. The study reach is located along the Cecina (Tuscany, Italy). Bank deposits were surveyed and grain size analyses were carried out for the main levels. In the monitoring reach, analytical and digital photogrammetry have been applied to verify the accuracy of measures and to compare advantages and disadvantages of each one. High-resolution terrestrial photogrammetry surveys were integrated with topographic measurements, repeated after each major flow events during the monitoring period. Rainfall and changes in river stage measured during flow events have been obtained and analyzed. Comparison between different surveys enabled precise calculation of the volumetric differences between them and the total volume of material eroded. The distribution and intensity of the erosion are illustrated through an erosion map of the bank surface."" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">A detailed study on riverbank retreat is reported with the aim to investigate on advantages and limitations of a high-resolution methodology such as terrestrial photogrammetry, and to quantify the sediment eroded from a representative reach of riverbank during a period of about 30 months. The study reach is located along the Cecina (Tuscany, Italy). Bank deposits were surveyed and grain size analyses were carried out for the main levels. In the monitoring reach, analytical and digital photogrammetry have been applied to verify the accuracy of measures and to compare advantages and disadvantages of each one. High-resolution terrestrial photogrammetry surveys were integrated with topographic measurements, repeated after each major flow events during the monitoring period. Rainfall and changes in river stage measured during flow events have been obtained and analyzed. Comparison between different surveys enabled precise calculation of the volumetric differences between them and the total volume of material eroded. The distribution and intensity of the erosion are illustrated through an erosion map of the bank surface.